From austerity to expansion? Consolidation, budget surpluses, and the decline of fiscal capacity - Lukas Haffert; Philip Mehrtens (Max Planck Institute for the Study of Societies, 2013)
In the wake of the financial crisis, most developed countries have entered a period of prolonged budgetary austerity. While the success of austerity programs is still unclear, it is also an open question what success would mean for activist government in the long run. This paper rejects the progressive belief that successful fiscal consolidation will lead to a strengthening of fiscal capacity, arguing that consolidations transform the political context in which fiscal policy is made. By analyzing the evolution of public expenditure in six countries with sustained budget surpluses, it shows that while surpluses were mostly achieved through expenditure cuts, they were predominantly used for cutting taxes. While fiscal crises abated, their collateral damage to public expenditure remained. This result is further elaborated by a case study of the Swedish budget surplus. The paper concludes that consolidations can create a specific type of fiscal regime and thus have long-term consequences for the fiscal capacity of the state. – – Angesichts der Schuldenprobleme in vielen entwickelten Ländern befinden sich die meisten von ihnen in einer Phase lang anhaltender Austerität. Und während noch völlig unklar ist, ob die Sparprogramme Erfolg haben, werden sie immer wieder mit dem Versprechen verbunden, erfolgreiche Konsolidierungen würden zu einer Wiedergewinnung staatlicher Handlungsfähigkeit führen. Diese Studie verwirft diese 'progressive Konsolidierungsthese' auf Basis einer theoretischen und empirischen Analyse. Ihr Argument lautet, dass Haushaltskonsolidierungen den Kontext, in dem Fiskalpolitik gemacht wird, dauerhaft verändern. Zwar erhöhen sie fiskalische Spielräume, zugleich aber schränken sie politische Spielräume ein. Anhand von sechs Ländern mit dauerhaften Haushaltsüberschüssen wird gezeigt, dass diese Überschüsse durch Ausgabenkürzungen erzielt, aber für Steuersenkungen verwendet wurden. Die Kollateralschäden der Konsolidierung blieben über Jahre in den Budgets sichtbar. Dieses Ergebnis wird von einer Fallstudie zu den schwedischen Haushaltsüberschüssen bestätigt. Das Fazit der Untersuchung ist, dass Konsolidierungen zu einem Wechsel des fiskalischen Regimes führen können, wodurch die staatliche Handlungsfähigkeit langfristig beschränkt wird. Überschüsse sind insofern nicht Ausdruck wachsender Gestaltungsfreiheit, sondern schrumpfender Ambitionen des Staates.
Keywords: 300